Risks of Misuse of Electronic Games on Children and Their Remedies from the Perspective of Islamic Education - Baniismail, Rasha Ahmad; Lababneh, Ayesh Ali (Journal of Humanities & Social Sciences, 2025)
This study aimed to identify the risks of the misuse of electronic games on children and their remedies from an Islamic educational perspective in the areas of creed, psychology, health, and social behavior. It also sought to provide proposed solutions to minimize these risks. To achieve the study's objectives, the descriptive-analytical method was employed by conducting open interviews with a sample of 25 experts selected from the Department of Islamic Education at the Faculty of Sharia and the Department of Counseling and Psychology at the Faculty of Education at Yarmouk University. For data analysis, the Miles and Huberman (1984) interview analysis model was used, which relies on three elements: data reduction, data display, and conclusion drawing/verification. Additionally, the reliability of interview data analysis was ensured by involving another researcher and applying Holsti's formula to confirm the stability of the analysis. The results of the interview analysis showed that the incorrect use of electronic games results in religious violations such as prostrating to an idol at a percentage of (40%), reviving the dead at a percentage of (24%), and getting used to watching some doctrinal violations at a percentage of (20%). The results showed many negative effects on the psychological level (loneliness at a percentage of (36%), isolation at a percentage of (32%), depression at a percentage of (32%), addiction at a percentage of (20%). On the health level, the effects were represented by obesity at a percentage of (32%), diseases of the spine and neck at a percentage of (32%), eye diseases and poor vision at a percentage of (20%), while on the social level, they were represented by violence at a percentage of (40%), the prevalence of aggressive spirit and aggressive behavior at a percentage of (32%), and getting used to scenes of nudity at a percentage of (16%).
Keywords: Risks; Electronic Games; Islamic Education; Children